2009
DOI: 10.4049/jimmunol.182.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Foxp3 in Regulatory T Cells Reflect Their Functional Status in Transplantation

Abstract: Foxp3 expressing CD4+CD25+ regulatory T cells (Tregs) have been shown to prevent allograft rejection in clinical and animal models of transplantation. However, the role of Foxp3 in regulating Treg function, and the kinetics and mechanism of action of Tregs in inducing allograft tolerance in transplantation, are still not fully understood. Thus, we investigated the kinetics and function of Tregs in a mouse model of orthotopic corneal transplantation, the most common form of tissue grafting worldwide. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
233
1
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(265 citation statements)
references
References 25 publications
19
233
1
12
Order By: Relevance
“…It is reported that CD4 + CD25 + FoxP3 + Tregs can be uniquely induced when orthotopic corneal allografts are transplanted to the eye 51, 52, 53. Furthermore, Tregs support long‐term corneal allograft survival 54, 55, 56, 57. Tregs can respond to interleukin‐17A (a proinflammatory cytokine), suppress the efferent arm of the immune response, and then enhance corneal allograft survival 55…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that CD4 + CD25 + FoxP3 + Tregs can be uniquely induced when orthotopic corneal allografts are transplanted to the eye 51, 52, 53. Furthermore, Tregs support long‐term corneal allograft survival 54, 55, 56, 57. Tregs can respond to interleukin‐17A (a proinflammatory cytokine), suppress the efferent arm of the immune response, and then enhance corneal allograft survival 55…”
Section: Discussionmentioning
confidence: 99%
“…However, as detailed by Chauhan et al (31), predicting and/or correlating allograft fate solely on the basis of Treg frequency may lead to inaccurate conclusions. It is therefore important to measure the levels of Foxp3 expression in parallel, with evidence that higher levels of Foxp3 expression are directly associated with an increased ability of Tregs to prevent graft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a clearly higher percentage of splenic CD4þFoxp3þ Tregs following third-party MSC treatment ( Figure 6A). Equally as important as the frequency of Foxp3-expressing Tregs is the level of Foxp3 expressed by these cells (31). To investigate this, we gated on the cell population of interest by forward scatter (FSC) and side scatter (SSC) parameters followed by doublet exclusion and subsequent gating based on expression of CD4 and CD25 ( Figure 6B).…”
Section: Analysis Of Immune Cell Distribution and Gene Expression In mentioning
confidence: 99%
“…CD4 + CD25 + T regs isolated from MS patients were found to have significantly reduced expression of Foxp3 23. Since the level of Foxp3 expression can impact suppressive function in vivo, 24 the ability of PSA to increase the MFI of Foxp3 provides further evidence that PSA could potentially reverse the functional defects characterized in the T reg population of MS patients. We also show that PSA can significantly increase the production of IL‐10.…”
Section: Discussionmentioning
confidence: 96%